2010
DOI: 10.2217/fmb.10.44
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Phenotypic Traits in Cryptococcus Varieties and Species and the Resulting Implications for Pathogenesis

Abstract: Variability of phenotypic characteristics in Cryptococcus neoformans var. grubii and var. neoformans as well as Cryptococcus gattii can have diverse effects on the virulence of these fungi and are thus important for pathogenesis. This article summarizes the diverse phenotypic changes that these fungi can manifest. We divide changes into those that affect the entire fungal population and are predominantly induced by environmental signals, and those that involve subpopulations of the fungal population and have t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 164 publications
0
20
1
Order By: Relevance
“…Microevolution and phenotypic variability of C. neoformans isolates occurs in the laboratory through multiple in vitro passages (reviewed by [42][44]). Therefore, an important factor considered in our experimental design when testing clinical isolates was the use of colonies isolated directly from CSF.…”
Section: Resultsmentioning
confidence: 99%
“…Microevolution and phenotypic variability of C. neoformans isolates occurs in the laboratory through multiple in vitro passages (reviewed by [42][44]). Therefore, an important factor considered in our experimental design when testing clinical isolates was the use of colonies isolated directly from CSF.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that during chronic infection with C. neoformans , phenotypic variants emerge [1014]. Such ‘microevolution’ has been documented in serial isolates [15,16] and experimental murine infection [17].…”
Section: Capsule Induction Is a Major Determinant Of Phenotypic Variamentioning
confidence: 99%
“…It includes at least 37 different species, of which two species namely, C.neoformans and C.gattii are recognized as important human and animal pathogens [17,18]. Rarely, other species of Cryptoccoccus such as C.albidus and C.laurentii are also reported to be of medical significance [9].…”
Section: Etiological Agentsmentioning
confidence: 99%